2015
DOI: 10.3892/or.2015.4125
|View full text |Cite
|
Sign up to set email alerts
|

Hypomethylated Rab27b is a progression-associated prognostic biomarker of glioma regulating MMP-9 to promote invasion

Abstract: In the present study, in order to analyze abnormalities in DNA methylation in glioma, we utilized a large cohort methylation microarray (119 glioma samples). Genes associated with tumor grade progression were screened through Significance Analysis of Microarrays (SAM) in the methylation microarray. We found that Rab27b was hypomethylated in high-grade glioma (anaplastic gliomas and glioblastomas) compared with low-grade glioma (astrocytoma, oligodendrocytoma and oligoastrocytoma) (p=0.02). In 52 glioma samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…Pu et al (23) demonstrated that miR-193a-3p and miR-193a-5p suppressed the metastasis of osteosarcoma cells via inhibition of RAB27B expression. Wang et al (16) reported that high expression of RAB27B was associated with the poor prognosis of patients with glioma, and knockdown of RAB27B significantly inhibited glioma U-87MG Uppsala and LN229 cell invasion, possibly owing to a reduction in matrix metallopeptidase 9 expression and activation. Additionally, Wang et al (16) demonstrated that inhibition of RAB27B expression also reduced the tumor growth in vivo; their data also indicated that RAB27B acts as an oncogene in glioma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pu et al (23) demonstrated that miR-193a-3p and miR-193a-5p suppressed the metastasis of osteosarcoma cells via inhibition of RAB27B expression. Wang et al (16) reported that high expression of RAB27B was associated with the poor prognosis of patients with glioma, and knockdown of RAB27B significantly inhibited glioma U-87MG Uppsala and LN229 cell invasion, possibly owing to a reduction in matrix metallopeptidase 9 expression and activation. Additionally, Wang et al (16) demonstrated that inhibition of RAB27B expression also reduced the tumor growth in vivo; their data also indicated that RAB27B acts as an oncogene in glioma.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (16) reported that high expression of RAB27B was associated with the poor prognosis of patients with glioma, and knockdown of RAB27B significantly inhibited glioma U-87MG Uppsala and LN229 cell invasion, possibly owing to a reduction in matrix metallopeptidase 9 expression and activation. Additionally, Wang et al (16) demonstrated that inhibition of RAB27B expression also reduced the tumor growth in vivo; their data also indicated that RAB27B acts as an oncogene in glioma. The present study determined that overexpression of miR-599 caused a reduction in the expression of RAB27B in U251 cells, which further confirmed that miR-599 could directly bind to RAB27B mRNA and repress its translation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are several limitations in the present study. LN229 is a typical glioma cell line, and when compared with other GBM cells, there are no significant differences in adherence and proliferation capacity (39)(40)(41). However, in the current study, only one GBM cell line was used and there was no verification using animal models.…”
Section: Discussionmentioning
confidence: 88%
“…Functionally, oncogenes were found to modulate the proliferation, apoptosis and metastasis of glioma cells (24). Moreover, oncogenes were proposed as novel biomarkers and treatment targets for glioma (25). Therefore, elucidating the expression level, clinical significance and biological function of specific oncogene in glioma will greatly contribute to the diagnosis and treatment of glioma.…”
Section: Discussionmentioning
confidence: 99%